ADSORPTION OF CD(II) METAL IONS USING COMPOSITE ADSORBENT PAPAYA SEEDS-ALGINATE-MAGNETITE - Manullang, Beatrix
Cadmium is a metal commonly utilized in electroplating, stabilizers, and as a component in battery manufacturing. Disposal of cadmium-containing waste into water bodies leads to a decline in water quality, posing a hazard to aquatic life. Solvent extraction, ion exchange, precipitation, and adsorption are among the methods employed to eliminate cadmium ions from its solutions. In this study, a papaya seed-alginate-magnetite (BAM) composite was synthesized as an adsorbent for the adsorption of Cd(II) metal ions. Adsorption was chosen as the method due to its cost-effectiveness, efficiency, and environmental friendliness. The synthesized adsorbent was characterized using Fourier Transform Infrared Spectroscopy (FTIR), X-ray diffraction (XRD), Scanning Electron Microscopy (SEM), and Energy Dispersive Spectroscopy (EDS). Shift patterns in the wave numbers of the FTIR spectrum indicated that carboxylate, carbonyl, and hydroxyl groups played a role in the Cd(II) ion adsorption process. Based on XRD characterization, it was revealed that magnetite had an average particle size of 10,67 nm and a crystallinity degree of 56.88%. The adsorption of Cd (II) metal ions using 50 mg/g of BAM composite, with an initial concentration of 20 ppm at a stirring speed of 150 rpm, was achieved at pH 4 and a contact time of 4 hours. The adsorption of Cd(II) metal ions using BAM composite followed a pseudo-second-order kinetic model and the Langmuir isotherm model with a maximum adsorption capacity of 11.12 mg/g. The adsorption process occurred spontaneously and endothermic.